Ex Ante Evaluation Of The Liability Company Policy Of State-Owned Enterprises (Soe) Jasa Tirta Ii In The Aspect Of Public Services Using The Cost Benefit Analysis (CBA) Method - Wulandari, Ervina; Rahmatunnisa, Mudiyati; Karlina, Nina (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
The changes in the global economy and competitive business growth demand increased efficiency, effectiveness, and professionalism in all business lines of SOEs, including Jasa Tirta II. In order to realize this, the Ministry of SOEs conducts SOE development, namely business model restructuring, including the stipulation of Government Regulation Number 113 of 2021 concerning Amendments to Government Regulation Number 25 of 1976 concerning State Capital Participation of the Republic of Indonesia for the Establishment of the Company (Persero) "Danareksa". The implication of the regulation is that the Jasa Tirta II Public Company as a company engaged in the field of water resources is included in the company that is planned to become a member of the Danareksa Holding so that it requires preparations to support the formation of the Danareksa Holding with the participation of state capital through the shift or transfer of shares in a subsidiary of a state-owned enterprise or a Limited Liability Company. Jasa Tirta II with the status of a business entity in the form of a Public Company certainly cannot shift or transfer shares, so Jasa Tirta II is considered necessary to change the status from a public company to a Limited Liability Company. Jasa Tirta II as a business entity assigned by the Government in terms of public benefit services in the field of Water Resources management, of course, this public service is one of the main activities that must be maintained by Jasa Tirta II. Therefore, there needs to be a study that specifically explores the possible impact of the policy of changing the status of business entities from public company to liability company with a point of view from the aspect of public services. The research conducted is an ex ante evaluation using an experimental quantitative approach that can be proven by the cost benefit analysis method. The stages is to identification the costs and benefits in the aspect of Jasa Tirta II's public services from the public company side and from the side if the business entity changes its form into a liability company, then processed by net benefit evaluation using the B/C Ratio and simulations the cost and benefit data for the next 10 years with an estimated Net Present Value (NVP) and Return on Investment (ROI). The net evaluation of benefits, which is a ratio to measure the benefits obtained by business entities, especially for the public service aspect of Jasa Tirta II from the side of public companies and the side of liability companies, obtained the result that from the side of public companies has more public service benefits of 2.64% compared to the benefits of public services from the side of liability companies which is 0.90%. As for the NVP simulation, it was found that the total net value of NVP from the side of the general company was Rp. 10,144,877,000,000,-, while the total net value of NVP from the side of the limited liability company was Rp. -827,508,000,000,-. And for the ROI simulation, it was obtained that the total net ROI for the public company Jasa Tirta II was 164%, while the total net ROI result if Jasa Tirta II was in the form of a liability company was -9.7%. Based on the results of the B/C Ratio, NVP and ROI simulations, it was concluded that Jasa Tirta with the form of a public company has a very positive impact and has greater public benefits from its public service aspect, while if the form of Jasa Tirta II business entity is a liability company, the benefits of public services have a negative impact or have not been maximized in fulfilling their general benefits.